(untitled) (University Journal of Zoology, Rajshahi University, 2012)
A study on the conservation on breeding colonies of bank myna, Acridotheres ginginianus (Latham 1790), was conducted in Chapai Nawabganj district of Bangladesh during a period from June 2007 to October 2009. The total population in the breeding colonies was estimated as 4,452. The preferable breeding habitats of bird are bank of the river, soil heap/ditches of brickfield and holes of culvert. Environmental calamities such as bank erosion and flooding, drought and rain affect the breeding colonies. Human settlement near breeding habitats, hunting, collecting eggs and nestlings by children, and use of nets to prevent nesting at bank of the river are the main human impacts on the breeding colonies. Major threats are flood, children-fun, predators and human for its meat. Conservation awareness for this species have depicted in this paper. DOI: http://dx.doi.org/10.3329/ujzru.v30i0.10753 Univ. j. zool. Rajshahi Univ. Vol. 30, 2011 pp. 49-53